1972
DOI: 10.1042/bj1270865
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular distribution of serum albumin and its possible precursors in rat liver

Abstract: 1. The fractionation of intracellular albumin labelled with radioactive l-leucine was studied in rat liver by means of isoelectric focusing. 2. Isoelectric fractionation was compared with ion-exchange chromatography for purification of radioactive intracellular albumin obtained by antibody precipitation. Similar results were obtained with both methods of separation. Purified albumin contains only a minor amount of the radioactivity. The remainder is associated with albumin-like protein(s). 3. The albumin-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1973
1973
1987
1987

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 13 publications
(29 reference statements)
1
24
0
Order By: Relevance
“…The material present in the immunc tates has properties compatible with those bumin precursor-proalbumin (31,42,43 [44], and alcohol dehydrogenase [45]) is unchanged or decreased in ethanol-fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…The material present in the immunc tates has properties compatible with those bumin precursor-proalbumin (31,42,43 [44], and alcohol dehydrogenase [45]) is unchanged or decreased in ethanol-fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the presence in these tissues of a protein similar to albumin [6,7,9,10]. When applying appropriate purification procedures, Judah and Nicholls observed that liver slices continued to incorporate ['4C]leucine into albumin after incorporation into total protein had been interrupted by cycloheximide or excess unlabelled leucine [Ill.…”
mentioning
confidence: 99%
“…In contrast to the easy isolation from serum, rather extensive purification is required to obtain pure albumin from biological material involved in albumin synthesis, such as liver [l-41, hepatoma [2,3], hepatocyte suspensions [ 5 ] , and cell-free proteinsynthesizing systems from liver [6-81. This is due to the presence in these tissues of a protein similar to albumin [6,7,9,10]. When applying appropriate purification procedures, Judah and Nicholls observed that liver slices continued to incorporate ['4C]leucine into albumin after incorporation into total protein had been interrupted by cycloheximide or excess unlabelled leucine [Ill.…”
mentioning
confidence: 99%
“…The term antialbumin-precipitable protein has been introduced to refer to the sum of albumin and its precursor proteins (Edwards et al, 1976a,b,c;Urban et al, 1976). Albumin can be separated from albumin-like proteins (precursors) by ion-exchange chromatography on DEAE-cellulose or on CM-cellulose Rotermund et al, 1970;Judah and Nicholls, 1971a;Geller et al, 1972;Judah et al, 1973;Urban et al, 1974a,b), electrophoresis in polyacrylamide gel Rotermund et al, 1970;Urban et al, 1974b), or cellulose acetate (Peters, 1977) and isoelectric focusing (Geller et al, 1972;Russell and Geller, 1975). An example for the separation of albumin and precursor albumin by chromatography on DEAE-cellulose is shown in Figures 3 and 4.…”
Section: Existence Of Precursor Albuminsmentioning
confidence: 99%